Mercury and the making of California : mining, landscape, and race, 1840-1890 - Johnston, Andrew Scott (Mining the American West., 2013)
Exploring the development of California, and the relationship between the built environments of the mercury-mining industry and the emerging ethnic identities and communities in California, this book brings mercury to its rightful place alongside gold and silver in their defining roles in the development of the American West. In this pioneering study, the author examines the history of California's mercury-mining industry - and its defining role in the making of the American West. Mercury was crucial to refining gold and silver; therefore, its production and use were vital to securing power and wealth in the West. The first industrialized mining in California, mercury mining had its own particular organization, structure, and built environments. These were formed within the Spanish Empire, subsequently transformed by British imperial ambitions, and eventually manipulated by American bankers and investors. In California, mercury mining also depended on a workforce differentiated by race and ethnicity. The landscapes of work and camp and the relations among the many groups involved in the industry - Mexicans, Chileans, Spanish, English, Irish, Cornish, American, and Chinese - form a crucial chapter in the complex history of race and ethnicity in the American West.